Thermodynamic Analysis of Quantum Otto Engines Exploring Qubit Efficiency in Non-Equilibrium Environments - Jeolous Malamula Nyasulu; Chunyang Wang; Zengxuan Zhao; Mushtaq Rana Imran (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2026)
This paper presents an analysis of quantum Otto heat engines operating out of equilibrium. It explores the fundamental thermodynamic principles governing these engines, focusing on efficiency, work output, and the impact of environmental factors, including thermal gradients, external fields, noise, and decoherence. The study investigates the effects of non-equilibrium conditions on engine performance, highlighting challenges and opportunities in practical realizations. Through numerical simulations, the article examines the power, efficiency, and performance coefficients, revealing trade-offs between these metrics and the influence of temperature differences and internal coupling strength. The results demonstrate that non-equilibrium effects can significantly reduce efficiency compared to idealized scenarios, underscoring the importance of accounting for both quantum effects and real-world constraints in the design and optimization of quantum heat engines. This work contributes to the growing body of knowledge in quantum thermodynamics, offering insights for quantum computing, sustainable energy technologies, and thermodynamic cycles at the quantum scale.